Knowledge Acquisition among Academics at a Malaysian Public University - Hussin, Md. Nasarudin (2007)
This study describes the knowledge acquisition of academicians at a local public university in Malaysia. This study is guided by four research questions: 1) the reasons for learning among academician in the context of academician practice 2) types of learning do academician learns in acquiring knowledge 3) factors influence and inhibit learning for knowledge acquisition among academician 4) personal characteristic of academician and the implication of learning outcome to academicians. A qualitative research method was used in the study and the primary data were collected mainly through interviews using a semi structured question guide during the in-depth interview with twelve respondents by using purposive and snowballing techniques. Three reasons of learning for acquisition of knowledge among academician emerged from the study. All respondents believed that learning is part of the knowledge advancement that academicians must keep abreast with the environmental change. Learning is a lifelong. Learning should be continuous as the academicians need to updated their knowledge. Academicians need to keep abreast with the technology changes. The themes emerge from the academician's knowledge acquisition are: Academicians acquire knowledge through formal, non-formal and informal learning strategies such as conferences, seminar, by academic visit, industrial linkages. Sources of informal learning is through reading, discussion, sharing knowledge with student, and research. The three themes that motivate academicians for learning are: the quest for knowledge, academic performance and salary. There are some barriers that inhibits the process of learning among academicians such as time, costs infrastructure and management support. The characteristics of learner as open minded, hard working, good communication and interaction skill and patience also influence on their learning. The learning outcomes to academicians allow to keep abreast with environment changes, increase job performance, selfconfident, add experience, career development and personal satisfaction. Five conclusions are drawn from the study. Academicians took responsibility to learn, learning is lifelong process, use multiple strategies of learning, and their personal characteristic and motivation to learn influence their learning for knowledge. Recommendation are put forth for knowledge acquisition are foster positive attitude toward lifelong learning, foster workplace learning, stimulate exciting environment, encourage active and cooperative learning and facilitate technology infrastructure.